2014
DOI: 10.4149/bll_2014_069
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte apoptotic index and p53 expression in obstructive jaundice rats

Abstract: Objective: Obstructive jaundice is a serious disease. It can detoriate critical functions in the liver. Material and method: A total of 20 male Wistar-Albino rats were randomly allocated into two groups consisting of ten in each as follows: Group I (Control) was subjected to a sham operation isolating the bile duct. Group II(Study) was subjected to acute cholestasis induced by bile duct ligation with 4/0 silk suture from two different places and full fold cut between ligatures. On the 7th day, group II rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Both phenomena occur after only few hours of treatment, suggesting that bilirubin could play a major role in the regulation of the apoptotic related genes. This observation leads us to confirm our earlier observations about the pro-apoptotic role of bilirubin on osteoblastic cells [24] and other cell types and tissues [15][16]25,26]. Likewise, the relationship between LCA and apoptosis in different tissues and cell types has been widely demonstrated.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both phenomena occur after only few hours of treatment, suggesting that bilirubin could play a major role in the regulation of the apoptotic related genes. This observation leads us to confirm our earlier observations about the pro-apoptotic role of bilirubin on osteoblastic cells [24] and other cell types and tissues [15][16]25,26]. Likewise, the relationship between LCA and apoptosis in different tissues and cell types has been widely demonstrated.…”
Section: Discussionsupporting
confidence: 90%
“…Bilirubin (Sigma) stock solution of 1600 M was prepared just before use by dissolving bilirubin in 10 ml 0.01N NaOH under dim light as previously described [12,[15][16][17][18]. It was filtered through a sterile filter (0.22 m pore size) and adjusted to pH 7.2-7.4 with 0.1N HCl, if necessary.…”
Section: Experimental Bilirubin Solution Preparationmentioning
confidence: 99%
“…The experimental obstructive jaundice model used in the present study is an irreversible obstruction model which does not fully simulate the clinical course of obstructive jaundice in humans. However, this model is widely used in the literature for the evaluation of pathophysiology and the treatment of experimental obstructive jaundice [ 31 , 32 , 33 , 34 ]. Thus, we preferred to use this model in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a programmed mechanism of cell death caused by various physiological and pathological conditions characterized by DNA damage[4]. In 2014, Kosar et al[5] confirmed that serious cellular damage occurs in hepatocytes during OJ. If DNA damage in a cell cannot be resolved, apoptotic signaling mechanisms can be activated, forcing the cell to self-destruct[6].…”
Section: Introductionmentioning
confidence: 99%